Aerobic Biodegradation of Hydrocarbons in High Temperature and Saline Groundwater. Issue 2 (March 2014) - Kashir, Mansor; Barker, Jim; McGregor, Rick; Shouakar‐Stash, Orfan
<x xml:space="preserve">Abstract</x> A series of laboratory microcosm experiments and a field pilot test were performed to evaluate the potential for aerobic biodegradation of aromatic hydrocarbons and methyl tert‐butyl ether (MtBE; a common oxygenate additive in gasoline) in saline, high temperature (>30° C) groundwater. Aquifer, sediment, and groundwater samples from two sites, one in Canada and another in Saudi Arabia, were incubated for 106 days to evaluate the changes in select hydrocarbon and MtBE concentrations and microbial community structure. Almost complete biodegradation of the aromatic hydrocarbons was found in the Saudi Arabian microcosm samples whereas the Canadian microcosm samples showed no significant biodegradation during the laboratory testing. MtBE degradation was not observed in either set of microcosms. Denaturing gradient gel electrophoresis analyses showed that, while the Canadian microorganisms were the most diverse, they showed little response during incubation. The microbial communities for the Saudi Arabian sample contained significant numbers of microorganisms capable of hydrocarbon degradation which increased during incubation. Based on the laboratory results, pilot‐scale testing at the Saudi Arabian field site was carried out to evaluate the effectiveness of enhanced aerobic biodegradation on a high temperature, saline petroleum hydrocarbon plume. Dissolved oxygen was delivered to the subsurface using a series of oxygen diffusion emitters installed perpendicular to groundwater flow, which created a reactive zone. Results obtained from the seven‐month field trial indicated that all the target compounds decreased with removal percentages varying between 33 percent for the trimethylbenzenes to greater than 80 percent for the BTEX compounds. MtBE decreased 40 percent on average whereas naphthalene was reduced 85 percent on average. Examination of the microbial population upgradient and downgradient of the emitter reactive zone suggested that the bacteria population went from an anaerobic, sulfate‐reducing dominated population to one dominated by a heterotrophic aerobic bacteria dominant population. These studies illustrate that field aerobic biodegradation may exceed expectations derived from simple laboratory microcosm experiments. Also, high salinity and elevated groundwater temperature do not appear to inhibit in situ aerobic biorestoration. © 2014 Wiley Periodicals, Inc.